Towards an ethics of solidarity in Pam Muñoz Ryan’s Esperanza rising and Mañanaland - Fernández García, Andrea (International Journal of English Studies, 2026)
This paper explores the ethics of solidarity that pulses through Pam Muñoz Ryan’s Esperanza rising (2000) and Mañanaland (2020) as a response to the inherited colonial structures that shape the characters’ lifeworlds. Drawing on decolonial and postcolonial feminist frameworks, as well as Rubén Gaztambide-Fernández’s there modes of solidarity –relational, transitive, and creative–(2012), this ethical orientation foregrounds the protagonists’ development into socially committed and future-oriented adolescents. Through their journeys, they learn to inhabit the perspectives of others, interrogate beyond what is known, and build alliances across differences for the sake of a better future, thereby challenging the logic of coloniality. Ultimately, this paper highlights the timely contribution of these YA narratives in inviting young readers to imagine a more just and compassionate world, instilling a much-needed sense of hope in today’s increasingly polarized global landscape.